Green Crime in Mexico: A Collection of Case Studies - Arroyo-Quiroz, Ines; Wyatt, Tanya (Palgrave Studies in Green Criminology, 2018)
This collection is the first exploration into green crime in Mexico, offering a unique critique of the environmental problems facing Mexico today. Written by a diverse range of Mexican academics and practitioners from different career stages and various different disciplines, this edited volume exposes the corruption, power, and disregard for the environment through highly detailed and engaging case studies. The chapters are grouped into four categories: Environmental Degradation, Social and Environmental Justice, Wildlife Trafficking, and Non-compliance with Environmental Obligations, and are illuminated by rigorous original research. This book fills a substantial gap in knowledge about concerns that are important not only to the Mexican people and the wider region, but to anyone with an interest in the environmental issues facing the world today. To this end, the contributors hope to inspire other Mexicans to study and research green crimes as well as to influence scholars and practitioners across Central and South America who are facing similar environmental crises and challenges